Chapter 7: Machine learning in HR staffing - Meier, Florian; Laumer, Sven (Handbook of Research on Artificial Intelligence in Human Resource Management, 2022)
Effective human resources management (HRM) is a key component that firms need to establish in the modern economy. One task of HRM is staffing employees to open vacancies guided by organizational needs and requirements. However, human resources (HR) staffing comprises the net employee requirements necessary for day-to-day business and reserve requirements to cope with employee workplace absenteeism. Furthermore, staffing includes the available number of employees, subject to additional hires and employee attrition. Recent studies expounded the possible supportive role of modern technologies, such as Machine Learning (ML), for HR staffing tasks. In this chapter, we report a systematic literature review based on 65 pieces to elaborate the usage of ML in HR staffing. We focus on the prediction of net requirements and absenteeism, as well as hires and attrition. This investigation brought forth a dysbalance in the focus of conducted research, as most authors focus on predicting employee attrition, while only a few regard new hires. Additionally, no single best-suited ML method is prominent in HR staffing, as the predictions base on the availability of different data- and feature sizes. A majority of the reviewed papers solely use publicly available HR data for their predictions, limiting the real-world likelihood of actual work-related human behavior predictions.<br

Combining Different Product Recommendations: Is it Valuable to Present Substitute and Complementary Recommendations Simultaneously? - Horneber, David; Meier, Florian; Kaiser, Carolin; Unfried, Matthias; Laumer, Sven (Proceedings of the Thirty-Third European Conference on Information Systems (ECIS 2025), 2025)
In e-commerce, different types of recommendations are often used simultaneously on the same site. While their individual effects on product views and sales are known, the effects of combining them are unclear. Drawing on research on consumer preference formation, choice overload, and information foraging theory, we propose three hypotheses to explain how the combination of substitute and complementary recommendations affects product views and sales at the early and the late stage of the purchase process. We propose a randomized between-subjects field experiment in an online shop to empirically test our hypotheses. Our research contributes to the literature on the effectiveness of recommendations in e-commerce by providing a better understanding of how the interaction of different types of recommendations influences product views and sales at different purchase stages. The results of our ongoing research have important implications for e-commerce platforms on how to effectively employ different types of recommendations.

Employee Perception of Enforced Telework in the Context of the Covid-19 Pandemic - Mattes, Carolin; Meier, Florian; Laumer, Sven (Proceedings of the 2022 Computers and People Research Conference, 2022)

Exploring Users’ Moral Reasoning Processes and their Impact on the Continued Use of Algorithmic Systems - Horneber, David; Tang, Willi; Meier, Florian; Matzner, Martin (Proceedings of the 45th International Conference on Information Systems, 2024)
Keywords: Algorithmic Bias; Algorithmic Systems; Artificial Intelligence; Ethic; Moral Reasoning

Hybrides Arbeiten - Der große Wurf oder die große Depression? Studienreihe Zukunft der Arbeit - Ausgabe 1 - Laumer, Sven; Meier, Florian; Schwehn, Tim-Julian (2023)

Hybrid Leadership as a Balancing Act - Qualitative Insights from a Financial Institution - Schwehn, Tim-Julian; Meier, Florian; Laumer, Sven (Hawaii International Conference on System Sciences (HICSS), 2025)
We explore the challenges and dynamics of hybrid leadership in organizations transitioning from traditional on-site to hybrid work environments. Using a qualitative single case study approach, we conducted 23 semi-structured interviews with hybrid leaders and employees at a financial institution. Our findings reveal three core paradoxes: ‘change vs. normality’, ‘digital connectivity vs. digital separation’, and ‘trust boosting vs. trust challenging’. These paradoxes highlight the complex balance hybrid leaders must achieve between leveraging technology for efficiency and maintaining interpersonal connections and trust. We propose that hybrid leadership requires new skills and strategies to navigate these tensions effectively. The study contributes to theory and practice by highlighting how the three identified paradoxes impact hybrid work and hybrid leadership. Our findings underscore the importance of adopting both/and approaches to address the presented paradoxes of hybrid leadership in hybrid wor
Keywords: hybrid leadership; hybrid work; paradox theory; e-leadership; virtual leadership

Hybrid Work as the Holy Grail? The Influence of Telework Intensity on Envy and Professional Isolation - Meier, Florian (Proceedings of the 57th Hawaii International Conference on System Sciences, 2024)

The Relationship Between Profile Disclosure Breadth and Network Size on Professional Social Media: Gender as a Moderator - Schötteler, Sebastian; Meier, Florian; Gengler, Eva; Laumer, Sven (SIGMIS Database - the Data Base for Advances in Information Systems, 2025)

Uncovering the Necessary Hard- and Soft-Skills to Get IT Personnel Jobs: A Text Mining Approach - Meier, Florian; Laumer, Sven (Proceedings of the 2022 Computers and People Research Conference, 2022)
With digitalization disrupting organizations every day, the necessary skills to get a job in modern societies are changing rapidly. Individuals and educational institutions seek knowledge of what industry demands in terms of hard- and soft-skills to plan their next step in having these skills in their personal or educational portfolio. To find out which hard- and soft-skills play a key role in finding IT personnel jobs, we employ a text mining approach on job advertisement data and generate a framework for IT personnel jobs. After doing some standard preprocessing steps, we use topic modeling to generate our results and map those with the IT personnel framework. Our results show that three competencies' fields are relevant for IT personnel jobs, and hard-and soft-skills play both a major role in those. Depending on which competencies field one wants to explore, we highlighted the most necessary skills that may play a decisive role when applying for a job in that position. Our findings contribute to the stream of literature equipping both educational institutions and individuals with recommendations of the skills to include and focus on regarding IT personnel.<br

Under the Neurodivergent Umbrella - A Qualitative Exploration of Neurodivergence and Remote Work - Kuhn, Lisa; Meier, Florian (19th International Conference on Wirtschaftsinformatik, 2024)
Keywords: neuromixed collaboration; participatory research; remote work; tech- nostress; technorelief

“Us vs. Them”–A Qualitative Study on Group-Formation in Hybrid Meetings - Meier, Florian; Schwehn, Tim-Julian; Pauleck, Isabell (2024)